Plasmon-exciton strong coupling in an organic material - Imane Hamideddine; Noureddine Ben Afkir; Siham Refki; Shinji Hayashi; Zouheir Sekkat (Scientific Reports)
Abstract We report on strong coupling between surface plasmons and excitons in an optically nonmetallic excitonic dye-polymer material of different thicknesses. We carried experiments of angular scans of reflectivity from silver and dye-polymer layers in a Kretshmann-Raether configuration, and we obtained the dispersive dielectric constant of the dye solutions for different dye concentrations using Lorentz model. The data obtained from our experiments, i.e. from reflectometry and absorption and dielectric dispersion, was used to perform rigorous electromagnetic calculations and finite difference time domaine numerical simulations of reflectivity and electric field distribution at the layers. Reflectometry calculations yielded dispersion relations of hybrid modes of propagating surface plasmons and excitons. The latter exhibit anticrossing which is the signature of strong coupling. The energy of Rabi splitting, $$\:E_{Rabi}$$ , is sample dependent, and is in the $$\:173-215\:meV$$ range, consistent with previously published experimental values of $$\:E_{Rabi}$$ of the dye-polymer studied. The theoretical calculations and simulations support the experimental findings and demonstrate enhancement and subwavelength confinement of the optical field in the bulk of the dye-polymer film as well as at its surface. Strong coupling between surface plasmons and excitons is due to the field localization and enhancement as well as the sharp transition in the absorption spectrum of the excitonic material.